Development and Usability Evaluation of a Virtual Reality Isolation Nursing Education Program for Nursing Students - So Young Choi; Seung-Woo Oh; Seung Ju Oh; Hye Ju Yun; Hye Yeon Son; Min Hae Chung; Kyung Mi Kim (Journal of Fundamental Nursing Science, 2026)
Purpose: This study developed a 360-degree virtual reality (VR) isolation nursing education program and evaluated its usability among nursing students in terms of flow, empathy, and satisfaction. Methods: The 360-degree VR isolation nursing content was developed using the ADDIE model, which comprises analysis, design, development, implementation, and evaluation. The program was implemented with 20 second-year nursing students who had not yet completed clinical practicum. Usability was evaluated using structured questionnaires that assessed flow, empathy, and satisfaction. Results: The 360-degree VR isolation nursing content consisted of nine phases: initial preparation, verification of the prescription and medication preparation, donning of personal protective equipment, patient identification, intravenous medication administration, position change and skin assessment, fundamental nursing assessment and interventions, administration of nebulization therapy, and post-treatment reassessment. The mean scores were 4.46±0.58 for flow, 4.28±0.66 for empathy, and 4.49±0.54 for satisfaction, all measured on a 5-point scale. Conclusion: The 360-degree VR isolation nursing education program produced high scores for flow, empathy, and satisfaction among nursing students. These findings suggest that VR-based isolation nursing content can reproduce isolation-room environments that are difficult to access during routine clinical practicum and may serve as a complementary strategy for undergraduate isolation nursing and infection control education.